2010
DOI: 10.1007/s11999-009-1151-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypercholesterolemia on Rotator Cuff Disease

Abstract: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 14 publications
5
150
0
1
Order By: Relevance
“…Other system diseases have been associated with rotator cuff tearing as well as rotator cuff healing. Abboud et al [38] collected serum cholesterol and lipid profiles on patients with full-thickness rotator cuff tears and compared them to a control population. They determined that total cholesterol, triglycerides and lowdensity lipoprotein cholesterol concentrations were higher in patients with rotator cuff tears.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other system diseases have been associated with rotator cuff tearing as well as rotator cuff healing. Abboud et al [38] collected serum cholesterol and lipid profiles on patients with full-thickness rotator cuff tears and compared them to a control population. They determined that total cholesterol, triglycerides and lowdensity lipoprotein cholesterol concentrations were higher in patients with rotator cuff tears.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
“…Smoking was detrimental to healing Ⅳ Chung et al [14] Retrospective cohort 408 pts/37.2 mo CT arthrogram, US Bone mineral density, as well as FI of the infraspinatus and amount of retraction, was an independent determining factor affecting postoperative rotator cuff healing Ⅲ Abboud et al [38] Case [53] RCT 201 pts/38.5 mo…”
Section: Mrimentioning
confidence: 99%
“…Many studies were conducted in older populations with at least one analysis group >50 years of age (33)(34)(35)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). The range of symptom duration varied substantially within and across studies.…”
Section: Secondary Screen-quality Assessment Overviewmentioning
confidence: 99%
“…This study was performed in the western world and patients with rotator cuff tear were found to be hypercholesterolemic [4]. But there are no Indian studies done till now to find out Indian population also have cuff problem due to raised cholesterol.…”
Section: Introductionmentioning
confidence: 97%
“…Trauma and degenerative conditions can cause a tear [3]. Among rotator cuff group supraspinatus is most commonly found to involve [4]. Although degenerative tears are common [5], still exact cause is unclear.…”
Section: Introductionmentioning
confidence: 99%